Benefits of core strengthening exercise in osteoarthritis knee patients: a narrative review - Rastogi, Aavrati; B. Kalia, Roop; K. Meena, Pradeep (International Journal of Research in Medical Sciences, 2024)
Osteoarthritis is a degenerative joint disease results from breakdown of cartilage that covers the ends of bones in joint. Breakdown causes bones to rub each other leading to pain, stiffness, swelling, loss of function in joint and can be accompanied by synovitis with or without joint fluid effusion. Muscle atrophy may develop if patient was inactive and did not perform exercises, which will affect functionality and stability of joint including activities of daily life. The aim of the study was to evaluate current literature and provide comprehensive overview of benefits of core muscle strengthening exercise in managing OA. The objective of this study was to discuss effectiveness of core muscle strengthening exercise in reducing pain, improving physical function, and enhancing quality of life in individuals with osteoarthritis knee. A systematic search was conducted to identify all relevant studies related to core muscle strengthening, database such as Pubmed, Cochrane library, Scopus had been used. Studies demonstrating clinical importance of core strengthening in treatment of osteoarthritis knee are limited. By performing randomized controlled trials with a big sample size, new researchers should produce more unique findings.